Superstition and Folk Religion is Different - Chai, Elena Gregoria Chin Fern (Sin Chew Daily Kota Kinabalu, 2015)
Superstition and folk religion are two different beliefs. There could be some elements of superstitions in folk religion but it is not tantamount. Therefore it should not be perceived that folk religion is a superstitious belief.